Methodology for exploring SOFC system layouts in a highly integrated hybrid propulsion system - Mantelli, Luca; Dubey, Abhishek; Buzzola, Dario; Ferrari, Mario Luigi; Pontika, Evangelia; Kazula, Stefan; Ewald, Daniel; Weber, Andre; De Graaf, Stefanie (American Society of Mechanical Engineers (ASME), 2025)
This paper presents a methodology to compare different layouts of a solid oxide fuel cell (SOFC) system, focusing on component integration and constraints for low-emission aircraft propulsion. The SOFC system is a subsystem of an Integrated Power and Propulsion System (IPPS) fueled by hydrogen and tightly coupled with a micro gas turbine (mGT). The methodology presented here is applied to the case study of a mGT-SOFC and will later help to define the SOFC system layout for the 1MW+ IPPS of the FlyECO project. Due to the low power density of current SOFCs designed for stationary applications, technology projections are used to explore a scenario of entry into service in 2050. Parametric analyses have been performed to consider possible future developments and performance opportunities on the basis of anticipated increases in SOFC power density, which so far could only be implemented on a laboratory scale. Different SOFC system layouts are defined by assuming different aircraft operating conditions (take-off and cruise) as design point, due to the important impact of ambient pressure and temperature in-flight variation on the SOFC system, the related components and the overall performance. To maximize the synergy between SOFC and mGT, all layouts are based on a pressurized SOFC and include a heat exchanger for heat recovery and flow pre-heating. The system performance exploration is carried out with the W-TEMP software, varying the hybridization factor of the mGT-SOFC system between 5% and 20%, and comparing its performance to a baseline H2-fueled mGT. The results obtained for this performance exploration report details on the coupling aspects between the micro gas turbine and the SOFC system and show clearly the advantages of mGT-SOFC integration in terms of net efficiency and production of water, which can be used in the combustion chamber of the mGT to limit the formation of NOx. In conclusion, a procedure to preliminary estimate the mass of the main components in each layout is also presented, to assess how different choices in the design of the mGT-SOFC can affect its weight.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; SOFC; hybrid system; propulsion; aviation